Estimating the residual risk for HIV, HCV and HBV in different types of platelet concentrates in Germany. Issue 2 (21st October 2014) - an der Heiden, M.; Ritter, S.; Hamouda, O.; Offergeld, R.
<x xml:space="preserve">Abstract</x> Background and Objectives We estimated and compared the residual risks due to window‐period donations for pooled and apheresis platelets in Germany using a modification of a previously described statistical model. This model directly utilizes the reported interdonation intervals before a positive donation and reflects in this aspect the look‐back procedures used in haemovigilance. Materials and Methods Data from the German National Blood Donor Surveillance System for the years 2006–2012, including reports about donations from repeat donors with confirmed positive test results for HIV, HCV and HBV, were used to estimate the risk of undetected infectious units for both pooled and apheresis platelets. Results Demographics of whole‐blood and apheresis donors differed in age, gender, catchment area and interdonation interval. These differences impact on the prevalence and incidence of transfusion relevant infections and consequently the residual risk. The estimates for the residual risks for pooled and apheresis platelets were comparable. For HIV, there was no significant difference, for HCV apheresis platelets had a lower residual risk, whereas pooled platelets had a lower risk for undetected HBV infections. Conclusion These findings do not support calls for a shift to an apheresis platelets‐only policy in Germany.